Історичний контекст Обести: від Ємадикина до Коцупіївки - Тищенко, К.М. (Сіверщина в історії України, 2012)
Сумські й чернігівські топоніми як частину прадавнього
іранського фракталу назв стало можливим виділити й
прокоментувати після виявлення контурів цього фракталу
в масштабі цілої Україні і більше – у його «скіфських»
продовженнях до Балтійського узбережжя Польщі й Німеччини.
Конкретизації основних положень теми сприяли здобутки
іраністики й суміжних наук, а саме: з одного боку, виявлення
у топонімії України неодноразових повторень терміна
«сатрапія» і конкретний слід ХХIV перської сатрапії Сака
Парадрія «Скіфи заморські», – а з іншого боку, відповідність
такого сліду відомостям про цю сатрапію в царських написах Персеполіса. Додатковим аргументом на користь висновку про перський топонімічний слід в Україні стали дані генетики про поширеність серед українців і сусідніх народів носіїв «месопотамської» Y-гаплогрупи J2 (в Україні бл. 7 %). Сумские и черниговские топонимы как часть древнего
иранского фрактала названий стало возможным виделить
и прокомментировать после обнаружения контуров этого
фрактала в масштабе целой Украины и более – в его «скифских»
продолжениях до Балтийского побережья Польши и Германии.
Конкретизации основных положений темы способствовали
достижения иранистики и смежных наук, а именно: с одной
стороны, обнаружение в топонимии Украины неоднократных
повторений термина «сатрапия» и конкретный след ХХIV
персидской сатрапии Сака Парадрия «Скифы заморские», – а
с другой стороны, соответствие такого следа упоминаниям об
этой сатрапии в царских надписях Персеполиса. Дополнительным аргументом в пользу вывода о персидском топонимическом следе в Украине стали данные генетики о распространенности среди украинцев и соседних народов носителей «месопотамской» Y-гаплогруппы J2 (в Украине ок. 7 %). After the statement of general shape of Old Iranian traces area
in the place name system of Ukraine – with its “scythian” outlets
to the Baltic shore of Poland and Germany – it bacame possible
to systematize a part of this area situated in Sumy and Chernihiv
regions. The main lines of the paper were precised thanks to the
achievments of the Iranian studies as well as adjacent scientific
sectors. From one side, in the toponymic system of Ukraine were
detected some place names from the stem ‘satrap’ with other traces
of the ХХIV-th Persian satrapy of Sakā Paradriya (Paradraya).
From another side, it was demonstrated, that these place names
correspond to the real existence of this satrapy, proved by the
Royal inscriptions of Persepolis. a supplementary argument on
behalf of the possibility of Persian traces in the place name system
of Ukraine was the genetic information about the widespread of
“mesopotamian” Y-haplogroup J2 among Ukrainian and neigbour
ethnicities (ca. 7% in Ukraine).